(untitled) (American Journal of Multidisciplinary Research and Innovation, 2022)
A smartphone is a portable computer that combines a mobile phone and a computer into one device. Smartphones have more powerful hardware and robust mobile operating systems. They enable web browsing over mobile broadband, and multimedia functionality (including music, video, cameras, and gaming) in addition to basic phone features. Researcher Patrice Buzzanell claims resilience theory has five components that businesses can cultivate. These include creating normalcy, affirming identity anchors, utilizing communication networks, and putting alternative logic into practice. Business continuity planning, which tries to make organizations more resilient to failure, was developed with the help of resilience theory. Resilience theory places a strong emphasis on the fact that conflict arises naturally in larger groups of individuals. Management had similar views between the late 1940s and the middle of the 1970s. Excellent teamwork requires effective communication. Private Smartphone Retailer Wireless is a Boholano brand that debuted in 1994 and has since grown to include more than forty stores as well as an online store. The company’s name essentially sums up its mission: to serve Savers, end consumers seeking high-quality devices at the greatest prices. Crisis management is the process by which an organization deals with a disruptive and unexpected event. One of our best conflict resolution moves is to sort out and handle the situation quickly and informally. The effective and efficient administration of people inside a company or organization is known as human resource management. It is created to maximize worker performance in support of an employer’s strategic goals. The process starts with the hiring and selection process, followed by regularization and retention of the job. Branches serve as both after-sales centers and pick-up locations for online orders. They have changed the user experience to get to a point where customers can interact with brands both physically and virtually.